2020 News & Views: The changing outlook for food aid (Featured article) - International Food Policy Research Institute (International Food Policy Research Institute, 1998)
Table of Contents:; The Changing Outlook for Food Aid; 2020 In Brief : The Future of Pest Management and Food Production / Revitalizing Agricultural and Rural Development; Sub-Saharan African Networks Meet to Set 2020 Vision Priorities; 2020 Vision Committee Member Wins Nobel Prize; 2020 Views : The World Food Programme: On the Front Lines of the Fight against Hunger; 2020 Vision for South Asia Workshop; New Members Join 2020 International Advisory Committee